2020
DOI: 10.2478/aucft-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring in Vitro Antioxidant Activity and Physicochemical Properties of Selected Under-Exploited Tropical Fruits

Abstract: Dacryodes edulis (DE), Dalium guineensis (DG), Spondias mombin (SM) and Irvingia gabonensis (IG) as notable underexploited tropical wild fruits in Nigeria, were evaluated for quality characteristics, phenolic contents and in-vitro antioxidant activity. pH of the fruits ranked thus DE > IG > DG > SM and the reverse order was true for acidity. IG exhibited highest obrix, vitamin C and total sugar content. DE had no detectable reducing sugar compared to 18.84% in IG. Total phenol and flavonoid contents f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The edible portion of D. edulis is composed of 8.7% dietary fiber, 5% carbohydrates, 4% protein, and 22% oils; its vitamin C content was estimated at 14.11 mg/100 g of crude pulp extract but this composition varies according to some environmental factors [ 62 , 63 ]. The study of the mineral composition of its fruits showed that it is an important source of iron (4.91–8.67 mg/kg), sodium (51.54–108.01 mg/kg), potassium (552.39–646.05 mg/kg), magnesium (23.13–73.18 mg/kg), zinc (130.48–136.18 mg/kg, manganese (25.96–26.86 mg/kg) and calcium (531.31–1337.02 mg/kg), thus indicating the nutritional value of D. edulis fruits [ 64 , 65 , 66 ].…”
Section: Description Of Dacryodes Vahl Species And...mentioning
confidence: 99%
See 1 more Smart Citation
“…The edible portion of D. edulis is composed of 8.7% dietary fiber, 5% carbohydrates, 4% protein, and 22% oils; its vitamin C content was estimated at 14.11 mg/100 g of crude pulp extract but this composition varies according to some environmental factors [ 62 , 63 ]. The study of the mineral composition of its fruits showed that it is an important source of iron (4.91–8.67 mg/kg), sodium (51.54–108.01 mg/kg), potassium (552.39–646.05 mg/kg), magnesium (23.13–73.18 mg/kg), zinc (130.48–136.18 mg/kg, manganese (25.96–26.86 mg/kg) and calcium (531.31–1337.02 mg/kg), thus indicating the nutritional value of D. edulis fruits [ 64 , 65 , 66 ].…”
Section: Description Of Dacryodes Vahl Species And...mentioning
confidence: 99%
“…The defatted 50% ethanol extracts of each part of D. rostrata were assayed for their antioxidant activities. The seeds exhibited higher activities than peels followed by pulps, and this was following the phenolic contents of these parts [ 62 ]. The ethanol extract of seeds has also been found to contain higher antioxidant properties in comparison with that of pulp and peel extract [ 19 ].…”
Section: Bioactivity Studiesmentioning
confidence: 99%
“…XXV (2021), no. 1 However, alongside the choice of solvent used for extraction, the absence or presence of non-phenolic antioxidant metabolites that can reduce Folin-Ciocalteu may influence the total phenol concentration of plant extracts (Jolayemi et al, 2020). The high amounts of total phenol and total flavonoids of EOCC, as shown in Table 1, has strong implications for the (highly significantly) antioxidant and anti-inflammatory potential of EOCC, and this is in line with previous studies by Gebashe et al, (2020), Olaiya et al, (2016) and Godwin et al, (2014), on the phytochemical profile and therapeutic potentials of Cymbopogon citratus.…”
Section: In Vitro Antioxidant Activities Of Eoccmentioning
confidence: 99%
“…Fruit process derived co-products represents a source of bioactive compounds, as fibre, antioxidants, and prebiotics (Hernández-Alcantara et al, 2016). Also, under-exploited fruits can be as well source of phenolic compounds with antioxidant activity (Jolayemi et al, 2020). These agro-industrial coproducts can be employed as replacers of animal saturated fat, where antioxidants and antimicrobial may enhance meat product quality as well, helping the meat industry to meet consumers demands for healthier and shelf-stable meat products (Hygreeva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%